2002
DOI: 10.1038/ng952
|View full text |Cite|
|
Sign up to set email alerts
|

Distal ureter morphogenesis depends on epithelial cell remodeling mediated by vitamin A and Ret

Abstract: Almost 1% of human infants are born with urogenital abnormalities, many of which are linked to irregular connections between the distal ureters and the bladder. During development, ureters migrate by an unknown mechanism from their initial integration site in the Wolffian ducts up to the base of the bladder in a process that we call ureter maturation. Rara(-/-) Rarb2(-/-) mice display impaired vitamin A signaling and develop syndromic urogenital malformations similar to those that occur in humans, including re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
127
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(130 citation statements)
references
References 35 publications
3
127
0
Order By: Relevance
“…In situ hybridization was performed as previously described in developing (embryonic day 15.5) and adult kidneys by using digoxigenin-labeled riboprobes (19). cDNA encoding a fragment from mouse Prmt7 (GenBank entry no.…”
Section: Measurement Of Gene Expression By Real-time Pcrmentioning
confidence: 99%
“…In situ hybridization was performed as previously described in developing (embryonic day 15.5) and adult kidneys by using digoxigenin-labeled riboprobes (19). cDNA encoding a fragment from mouse Prmt7 (GenBank entry no.…”
Section: Measurement Of Gene Expression By Real-time Pcrmentioning
confidence: 99%
“…The phenotypes of gene knockout mice have revealed that several growth and signaling factor families play fundamental roles in reproductive and urogenital organ formation (Batourina et al, 2002;Doles et al, 2006;Haraguchi et al, 2001;Haraguchi et al, 2000;Huang et al, 2005;Jamin et al, 2002;Kobayashi and Behringer, 2003;Kondo et al, 1996;McMahon et al, 2003;Morgan et al, 2003;Perriton et al, 2002;Suzuki et al, 2003). Shh is expressed in the cloacal epithelia and is vital for the regulation of structures derived from the genital tubercle (GT) and the urogenital sinus, such as the external genitalia and the prostate, respectively (de Santa Barbara and Roberts, 2002;Freestone et al, 2003;Pu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…43,44 the part of the mesonephric duct between newly developed ureter and urogenital sinus is subsequently removed by apoptosis, 45 whereupon the free end of the developing ureter inserts into the bladder wall and the vesicoureteric valve is formed. 41,46,47 the mechanism of vur and subsequent reflux nephro pathy is based on the disruption of a proper valvular mechanism at the vesicoureteric junction, which leads to retrograde flow of urine into the ureter or kidney. this disruption is most likely the result of a shortened intravesical ureter, and an enlarged or malpositioned ureteric orifice.…”
Section: Vur Is a Complex Diseasementioning
confidence: 99%